New research directions in the institution-based view - Peng, Mike (2014)
This paper points out new directions for the deepening and broadening of the institution-based view, by drawing on three streams of research with which I have been involved recently: (1) outward foreign direct investment from emerging economies, (2) bankruptcy laws and entrepreneurship development, and (3) institution-based research focusing on Africa. Such deepening has been accomplished by enhancing our institutionbased understanding of foreign direct investment with a focus on emerging multinationals, while broadening has been done both substantively by probing into the impact of bankruptcy laws on entrepreneurship development around the world and geographically by calling for enhanced research attention on Africa via an institution-based lens.